Cutting into the abyss: the subtle knife as the pharmakon in Pullman's His Dark Materials - Blomquist, Gregory (My University, 2013)
The Subtle Knife as the Pharmakon in Pullman's His Dark Materials In Philip Pullman's His Dark Materials trilogy, the subtle knife (or Æsahættr, literally meaning "god-destroyer") is the most significant of the trilogy's three central instruments. It is both a tool and a weapon, a device which is capable of revealing the abyssal void between the parallel universes that combine to form Pullman's multiverse; and capable of repairing the damage done by the all-consuming nothingness it exposes. Almost counter-intuitive in nature, the tool aspect of the knife creates the negative consequences of its use, whereas the weapon aspect of the knife comes to signify the positive consequences of its use. Having the potential for both good and evil, construction and destruction, I argue the subtle knife is the pharmakon of Pullman's trilogy. Originally a term referred to by Jacques Derrida, the pharmakon is a paradoxical aspect of being both the poison and the cure, or a dissembler of binaries. The pharmakon does not represent evil anymore than it represents good; it is purely neutral and thus a neutralizing agent. [Honours thesis]
Keywords: Phillip Pullman; His Dark Materials